Inovasi dan Kreativitas Sebagai Kunci Keberhasilan Wirausaha di Era Ekonomi Digital - Dwi Syaputra; Ahmad Afandi (Aksi Nyata : Jurnal Pengabdian Sosial dan Kemanusiaan, 2025)
Community Service (KKN) is one method to implement the Tri Dharma of Higher Education through community service activities. The Independent KKN Project from the University of Muhammadiyah North Sumatra in 2025 was implemented in Dolok Kahean Village, Tapian Dolok District, Simalungun Regency, with the theme "Innovation and Creativity as Keys to Entrepreneurial Success in the Digital Economy Era. " The purpose of this study is to improve the ability of Micro, Small, and Medium Enterprises (MSMEs) actors in maximizing product marketing using digital marketing, with an emphasis on the use of photo and video content for business branding. The implementation methods of this activity include observation, interviews, socialization, and training in photography practices, editing, and digital content strategies. The results of this activity show an increase in knowledge and skills of MSME actors in creating promotional content, building brand identities (such as logos and product packaging), and utilizing social media as a marketing tool. In addition, social activities such as mutual cooperation, economic education in schools, and the creation of educational signs about waste also contribute to increasing social awareness in the community. The success of this activity was facilitated by community cooperation and support from village officials, while the main challenges were geographical conditions and limited transportation. Overall, this KKN activity had a positive impact on the development of local MSMEs, increased digital literacy, and strengthened the relationship between students and the village community, demonstrating the role of higher education institutions in community empowerment.